2016
DOI: 10.1212/cpj.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of first-line natalizumab vs IFN-β or glatiramer acetate in relapsing MS

Abstract: Background: We compared efficacy and treatment persistence in treatment-naive patients with relapsing-remitting multiple sclerosis (RRMS) initiating natalizumab compared with interferon-b (IFNb)/glatiramer acetate (GA) therapies, using propensity score-matched cohorts from observational multiple sclerosis registries. Methods: The study population initiated IFN-b/GA in the MSBase Registry or natalizumab in the Tysabri Observational Program, had $3 months of on-treatment follow-up, and had active RRMS, defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Our clinical validity and population impact results (Table 4, Figure 2), modeled for natalizumab with an adverse event frequency of 1.3% (maximal risk reported by the manufacturer, see Methods), show that at least a quarter of PML cases could be prevented. Natalizumab is a highly effective treatment for many MS patients and some would benefit from its use as a first line therapy, such as those with aggressive or early onset forms of the disease (21,(83)(84)(85). Furthermore, an MRI surveillance study suggests that therapy duration is potentially not a very effective risk stratification factor (8).…”
Section: Discussionmentioning
confidence: 99%
“…Our clinical validity and population impact results (Table 4, Figure 2), modeled for natalizumab with an adverse event frequency of 1.3% (maximal risk reported by the manufacturer, see Methods), show that at least a quarter of PML cases could be prevented. Natalizumab is a highly effective treatment for many MS patients and some would benefit from its use as a first line therapy, such as those with aggressive or early onset forms of the disease (21,(83)(84)(85). Furthermore, an MRI surveillance study suggests that therapy duration is potentially not a very effective risk stratification factor (8).…”
Section: Discussionmentioning
confidence: 99%
“…However, healthcare costs for DMT administration and management have never been tested in long-term real-life scenarios in relation to MS clinical outcomes. In previous observational studies trying to investigate the long-term efficacy of DMTs, Natalizumab determined more positive disease outcomes, compared with Interferon-beta or Glatiramer acetate, in a large propensity-matched cohort [28]. Similarly, the highest cumulative exposure (a parameter including both dosage and time) to Interferon beta-1a treatment had more beneficial effects on long-term outcomes, compared to the lowest, in patients with similar baseline clinical features [6].…”
Section: Discussionmentioning
confidence: 99%
“…Propensity score analysis of a large cohort of patients with relapsing remitting multiple sclerosis found that natalizumab was superior to interferon beta and glatiramer acetate in terms of improved outcomes. 28…”
Section: Propensity Score Matchingmentioning
confidence: 99%